The Effect of Leverage, Liquidity and Total Asset Turnover on Financial Performance (A Case Study of Property & Real Estate Sector Companies for the 2020–2024 Period) - Putri Shofi Adilla; Nurul Kamila (Indo Publishing, 2026)
The property and real estate sector are important industries that reflects national economic conditions and corporate performance through the ability to generate profits. However, fluctuations in the financial performance of companies in this sector indicate the need to analyze the financial factors that influence it. This study aims to examine the effect of leverage measured by Debt to Equity Ratio (DER), liquidity measured by Current Ratio (CR), and activity measured by Total Asset Turnover (TATO) on financial performance measured by Return on Assets (ROA) of property and real estate companies listed on the Indonesia Stock Exchange during the 2020–2024 period. This research uses a quantitative approach with secondary data obtained from annual financial reports. Purposive sampling resulted in 24 companies with a total of 120 observations. Data was analyzed using multiple linear regression, classical assumption tests, coefficient of determination, t-test and F-test using IBM SPSS Statistics version 27. The results show that partially DER and CR have no significant effect on ROA, while TATO has a positive and significant effect on ROA. Simultaneously, the three variables have a significant effect on financial performance.